2018
DOI: 10.1039/c7sc04353h
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of ionic liquids to tune the polymorphic outcome of organic compounds

Abstract: The adoption of ionic liquids as crystallization solvents for polymorphic screening opens a new window for the applications of ILs, which may allow one to access the forms difficult to crystallize from organic solvents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 37 publications
(40 reference statements)
0
32
0
Order By: Relevance
“…At present, the structural relevance between solute selfassemblies in solution and molecular synthons in the resultant crystals is of great interest (Parveen et al, 2005;Burton et al, 2010;Tang et al, 2017;Zeng et al, 2018) and could shed light on how nucleation proceeds. For instance, it was found that the formation of two conformational polymorphs of Nphenylhydroxamic acid had direct correspondence with the dominant conformers in two different solvents (Yamasaki et al, 2006;Ischenko et al, 2005), which suggested a simple nucleation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the structural relevance between solute selfassemblies in solution and molecular synthons in the resultant crystals is of great interest (Parveen et al, 2005;Burton et al, 2010;Tang et al, 2017;Zeng et al, 2018) and could shed light on how nucleation proceeds. For instance, it was found that the formation of two conformational polymorphs of Nphenylhydroxamic acid had direct correspondence with the dominant conformers in two different solvents (Yamasaki et al, 2006;Ischenko et al, 2005), which suggested a simple nucleation pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To counteract the disadvantages of solid drugs, new ILs could be linked with pharmacologically active ingredients, forming API-ILs, an alternative to common crystalline salts [ 24 , 27 , 28 , 31 , 38 , 40 , 43 ]. The possibility to eliminate or reduce the negative side effects of an active compound by delivering it as an API–IL is attractive for pharmaceutical, environmental, and medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…The nearly infinite combinations of suitable cations and anions allow for a wide range of modulation of the IL properties [ 39 , 40 , 41 , 42 ]. The anion is usually responsible for characteristics such as air and water stability, and the cation is usually responsible for the melting temperature and organic solubility [ 43 ].…”
Section: Ionic Liquids and Active Pharmaceutical Ingredients (Apismentioning
confidence: 99%
“…17 Although these types of interactions are complex in nature, recently we have shown that the effect of certain ILs can be studied with respect to crystallization and polymorphism. 18,19 In analogy with the POLAG approach as mentioned above, we hypothesized that changing the structural variables of suitable ILs by changing either of the components may give us access to desirable cocrystals. While the chain length of the EG derivatives could be only variable in POLAG, the structural variables of ILs can be controlled either by individual tuning of the components or in a dual manner, increasing the number of variables in the grinding process.…”
mentioning
confidence: 99%
“…We chose imidazolium-based ILs with relatively inert anions as grinding liquids because of their utility in crystallization of small molecules in previous studies. 19 While previous studies employed different solvents or polymers of varying chain lengths, the focus of our strategy involved tuning the ILs either by modifying the substitution on the imidazolium cation or by changing the anions. The ILs studied, 26 ).…”
mentioning
confidence: 99%